2018
DOI: 10.3389/fphys.2018.01571
|View full text |Cite
|
Sign up to set email alerts
|

Different Statistical Approaches to Characterization of Adipocyte Size in Offspring of Obese Rats: Effects of Maternal or Offspring Exercise Intervention

Abstract: Adipocyte size (AS) shows asymmetric distribution related to current metabolic state, e.g., adipogenesis or lipolysis. We profiled AS distribution using different statistical approaches in offspring (F1) of control (C) and obese (MO) mothers (F0) with and without F0 or F1 exercise. Offspring from F0 exercise were designated CF0ex and MOF0ex. Exercised F1 of sedentary mothers were designated CF1ex and MOF1ex. F1 retroperitoneal fat cross-sectional AS was measured by median, cumulative distributions, data disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 62 publications
6
40
0
Order By: Relevance
“…Our data indicate that histology-derived adipocyte cross-sectional area is characterized by positive skewness. Similar distribution shapes have been previously reported in rodents and humans [ 8 , 39 , 40 ]. We show that calculation of adipocyte diameter, volume or surface area from cross-sectional area introduces substantial changes to distribution shape.…”
Section: Discussionsupporting
confidence: 87%
“…Our data indicate that histology-derived adipocyte cross-sectional area is characterized by positive skewness. Similar distribution shapes have been previously reported in rodents and humans [ 8 , 39 , 40 ]. We show that calculation of adipocyte diameter, volume or surface area from cross-sectional area introduces substantial changes to distribution shape.…”
Section: Discussionsupporting
confidence: 87%
“…Studies examining the frequency distribution of adipose cells showed that adipocytes are not homogeneous in their ability to uptake lipids or their functional properties in response to a high-fat diet [45]. Ibáñez et al [46] explained that asymmetry in cell distribution is a critical outcome of proliferation and differentiation since small adipocytes are linked to an increased rate of adipocyte proliferation, and large adipocytes are associated with increased lipid storage capacity. The novel findings from this study are that HPD-Control displayed a nearly bimodal distribution of adipose cells, which suggests that high-protein diets associated with sedentarism can increase both mature and immature cells or cells incapable of maximally depositing triglyceride.…”
Section: Discussionmentioning
confidence: 99%
“…In stark contrast, a lack of change in the phosphorylation states of AKT, mTOR, ERK, GSK3B, and S6K during fetal life as well as increased mRNA expression of IR2, mTOR, AKT, PI3K, and peroxisome proliferator-activated receptor gamma (PPARγ) in the VAT with increased insulinstimulated phosphorylated-AKT in the VAT and SAT in adult female offspring of gestationally testosterone-treated sheep (Nada et al 2010) reflect an insulinsensitive state in adipose tissue. Whether these differences in adipose insulin sensitivity programmed by gestational insults is due to differences in the adipose depot examined, species-or sex-specific differences, developmental time point studied, or differences in adipocyte differentiation (adipocyte hypertrophy in PCOS and offspring of obese mice (Manneras-Holm et al 2011, Caldwell et al 2014, Ibanez et al 2018) vs adipocyte hypotrophy in gestational testosterone-treated sheep (Cardoso et al 2016)) requires further examination.…”
Section: Adiposementioning
confidence: 99%